Correlation between D-dimer and computed tomography severity score in middle aged young adults with COVID-19 pneumonia: a retrospective study - A., Deepak Kumar; Solanke, Sachin N. (International Journal of Advances in Medicine, 2021)
Background: An unknown pneumonia broke out in Wuhan City in December 2019 and it was confirmed as an acute respiratory infectious disease caused by Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2, formerly known as 2019-nCoV). Consumption coagulopathy, which should be obviated in order to decrease mortality, arises in disseminated intravascular coagulation with a decrease in fibrinogen and an increase in D-dimer levels. However, studies on the predictive and prognostic values of coagulation parameters in the setting of patients with COVID-19 are still limited. The objective of this retrospective study was to investigate the correlation of D-dimer and computed tomography severity score in patients with COVID-19 pneumonia. Methods: The present retrospective study was conducted among 108 subjects reported COVID RT-PCR positive admitted during the study period i.e.; January-August 2021 in the department of medicine of Rural Medical College, Loni. Pneumonia was confirmed by Computed tomography (CT) examination and coagulation test completed within 12 hr after admission were enrolled. Coagulation tests, which Fibrinogen (Fib) and D-dimer were performed. CT score was categorized into mild (0-7), moderate (8-16) and advanced grade (17-25 points). Results: The mean age of male and female was 38.52±5.34 and 35.67±3.22 years respectively, with an overall age of 37.79±4.58 years. Mean D-dimer level was 0.54±0.09, 0.91±0.22 and 1.96±0.47 mcg/ml among subjects having mild, moderate and severe CT score respectively. According to multivariate analysis, higher D-dimer (OR:3.61, p<0.01) was significantly associated with CT severity score. Conclusions: Study concluded that the D-dimer level's time point was matched to the time of CT scan, we have reasons to correlate that the D-dimer level may predict the severity of inflammation prior to coagulopathy/thrombosis.